تحقيق مخطوطة "مختصر تيسير الطالب لنيل المراتب"لأبي الفتح محمد بن عبد القادر بن صالح بن عبد الرحيم بن محمد الخطيب الحسني الشافعي المتوفى سنه 1315 هـ: A Brief Facilitation of the Student to Obtain Ranks” by Abu Al-Fath Muhammad bin Abdul-Qadir bin Salih bin Abdul-Rahim bin Muhammad Al-Khatib Al-Hasani Al-Shafi’i, Who Died in The Year 1315 Ah - Abdullah Hashim, Alsharif Hashim; Ali Hassan, Elsayed Makki Elbishr (SIBAWAYH Arabic Language and Education, 2024)
إن أهمية المخطوطات وتحقيقها لدى الباحثين يشكِّل دورا كبيرا في إثراء المعلومات وشرح المجملات وتقعيد المسائل وبسط الحقائق. والواقع يكشف لنا أن كثيرا من المخطوطات لا زالت حبيسة الأدراج إلا ما كان من جهود بعض العلماء والباحثين الذين اعتنوا بها وأظهروها للنور؛ فكانت مشكلة البحث مرتكزة على ثلاثة أمور: الأول: دور المخطوطات في إبراز العلماء الأوائل وإبراز علمهم الغزير. والثاني: احتياج مركز البحوث والمخطوطات بسلطنة عمان إلى اقتناء المخطوطات وتحقيقها. والثالث: مكانة صاحب المخطوطة ودوره الإثرائي في المكتبة النحوية وإبراز جهود علماء الأمة الإسلامية. واعتمدت أسئلة الدراسة على نقاط أساسية منها: مدى صحة نسبة المخطوطة إلى صاحبها، ومصداقية المصادر التي استخدمها، وما هو سبب وجود الفروق في المخطوطات الثلاث. وتكمن أهمية موضوع المخطوطة في مؤلفها وقامته النحوية، وأنها لم تحقق بعد، وفي شرح متن العوامل للبركوي أيضا وأهميته العلمية ودوره في إثراء المكتبة النحوية.واستفاد الباحث من الدراسات السابقة التي اعتنت بالمخطوطات ومنهجية تحقيقها، واتبع أيضا المنهج الوصفي والارتباطي من خلال دراسة حياة المؤلف العلمية والاجتماعية والسياسية، وكذلك تتطرق إلى المنهج التحليلي من خلال المقارنات بين النسخ، وبيان مواطن الاختلاف والصواب فيما بينها. ووضح الباحث كذلك منهجه في التعامل مع المخطوطة من حيث الخط والفروقات والأخطاء اللغوية والمصطلحات والرموز التي سار عليها في تحقيقه. وأبرز دور العوامل وأهمية تدريسها، وقارن بين الفروقات التي في منهج البركوي والجرجاني، وبدأ مؤلف المخطوطة في شرح العوامل للبركوي فشرح المقدمة والعامل وتقسيماته، وأعرب الأمثلة وهذا مما يميز الشرح بكثرة التطبيقات الإعرابية، وتطرقه للفوائد النحوية والدينية. وبيَّن أنه لابد لكل طالب علم معرفة الإعراب، وأن العوامل مئة عامل بالجملة، منها ستون عاملا، وثلاثون معمولا، وعشرة عملا وإعرابا، مع ضرب الأمثلة، وشرحها وإعرابها ؛ فضلا عن الفوائد والدرر والنكت الكثيرة والمتناثرة، ومن التوصيات والنتائج التي توصل لها الباحث الاعتناء بالمخطوطات ولا سيما من قبل الجامعات وتكليف بعض طلبة الدراسات العليا في تحقيقها حيث إنهم يستطيعون استخراج عددا كبيرا من المخطوطات المخزنة في الأرفف، وأن هناك قواعد معنية بكيفية تحقيق المخطوطات، وأن المخطوطة التي حققها الباحث هي لصاحبها أبي الفتح محمد بن عبد القادر بن صالح الخطيب الحسني، حيث ذكر ناسخوها ذلك في آخر نسخهم؛ فضلا عمن ترجم للمؤلف بأنها من مؤلفاته.The significance of manuscripts and their manuscriptology among researchers plays an essential role in enriching information, explaining gross issues, grammarising matters and spreading facts. Reality reveals to us that many manuscripts are still trapped in drawers, except for the efforts exerted by some scholars and researchers who had looked after them and showed them under spotlight. This has benefited both researchers and scientific libraries and have turned out to be reliable sources to get knowledge from. However, the work and attention paid it remains very little. The problem of this current research has based on three corners: Firstly, the role of manuscripts in highlighting early scholars and their prolific knowledge, Secondly, The Sultanate of Oman's Research and Manuscript Centre needs to acquire and verify manuscripts, and Thirdly, the position of the author of the manuscript and his enrichment role in the grammar library and highlighting the efforts of the scholars of the Islamic nation. The study's questions banked on key points, including the validity of the manuscript's attribution to its owner, the credibility of the sources it had used, and the reason behind the differences in the three manuscripts. The importance of the subject of the manuscript lies in its author and his grammarian prestige and that it has not yet been manuscriptologised, accordingly it should be cared for and to be manuscriptologised and in explaining the Al Barkawi’s Elements’ Corpus, too and its scientific significance and role in enriching the grammar library. The researcher has benefited from previous studies that cared for manuscripts and their manuscriptology methodology and how to address some of the difficulties that often hinder the manuscriptologist. The researcher adopted the descriptive and associative approach by studying the author's scientific, social and political life. He also occasionally followed the analytical approach through holding comparisons among copies, indicating their differences and correctness. The researcher further illuminated his approach to handling the manuscript in terms of calligraphy, discrepancies, linguistic errors, terminology and symbols he had followed in manuscriptologising it. He emphasized the role of elements and the significance of their teaching, comparing the differences in the Al Barkawi and Al Jorjani curriculum. The author of the manuscript began explaining the Al Barkawi’s Elements, explaining the introduction and the Element and its divisions, parsed examples. So, explanation is characterized by the abundance of parsing applications and his turning to the grammatical and religious benefits, in clear details without shortage or deficiency. He explained that every student must know the inflection and that the Elements are a hundred in total, including (Sixty) 60 Elements, (Thirty) 30 Governess and (Ten) 10 Governments and parsing. He mentioned their divisions along with examples- giving, their explanation and parsing as word for word, which made them distinguished from the rest of the Elements- and grasped fully the explanation of Al Barkawi’s Elements Corpus as well as the many and scattered benefits, jewels and jokes. One of recommendations and conclusions  reached by the researcher is to take care of the manuscripts, especially through universities, and to assign some graduate- students to manuscriptologise them so that they can extract a large number of manuscripts stored in the shelves ,to show this heritage clearly and visibly to the nation, and  to be informed by the light of knowledge and illuminated by the information of ancestors.Keywords: Manuscriptology, Elements, Grammarising, Significance, inability